1996
DOI: 10.1007/bf02789166
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between tissue uptake of lead and iron in normal and iron-deficient rats during development

Abstract: Environmental lead intoxication, which frequently causes neurological disturbances, and iron deficiency are clinical problems commonly found in children. Also, iron deficiency has been shown to augment lead absorption from the intestine. Hence, there is evidence for an interaction between lead and iron metabolism which could produce changes in lead and iron uptake by the brain and other tissues. These possibilities were investigated using 15-, 21-, and 63-old rats with varying nutritional iron and lead status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Because heavier women are unlikely to gain as much weight and arm circumference as smaller ones, gain becomes an especially Our analysis of maternal diet provides new information on nutrient-lead interactions because it pertains to the transfer of lead from mother to fetus whereas most published research examines relationships of dietary intake and lead levels in either adults or children. In the APILS sample, higher maternal intakes of iron are associated with lower neonatal lead levels, a finding consistent with results from both experimental animal studies (Barton et al 1978;Crowe and Morgan 1996;Hamilton 1978;Hashmi et al 1989aHashmi et al , 1989bKlauder and Petering 1975;Mahaffey-Six and Goyer 1972;Ragan 1977;Shukla et al 1990;Singh et al 1991;Suzuki and Yoshida 1979) and human studies (Cheng et al 1998;Hammad et al 1996;Mahaffey and Annest 1986;Markowitz et al 1990;Szold 1974;Watson et al 1980Watson et al , 1986Wright et al 1999;Yip et al 1981;Yip and Dallman 1984) that have shown negative associations between iron intake or iron status and blood lead levels. Despite this negative relationship between maternal dietary iron and infant lead levels, we found no significant association between mother's iron stores (serum ferritin) and newborn's blood lead levels in bivariate or multivariate analysis (data not shown), mirroring the results of Milman and colleagues (1988).…”
Section: Discussionsupporting
confidence: 83%
“…Because heavier women are unlikely to gain as much weight and arm circumference as smaller ones, gain becomes an especially Our analysis of maternal diet provides new information on nutrient-lead interactions because it pertains to the transfer of lead from mother to fetus whereas most published research examines relationships of dietary intake and lead levels in either adults or children. In the APILS sample, higher maternal intakes of iron are associated with lower neonatal lead levels, a finding consistent with results from both experimental animal studies (Barton et al 1978;Crowe and Morgan 1996;Hamilton 1978;Hashmi et al 1989aHashmi et al , 1989bKlauder and Petering 1975;Mahaffey-Six and Goyer 1972;Ragan 1977;Shukla et al 1990;Singh et al 1991;Suzuki and Yoshida 1979) and human studies (Cheng et al 1998;Hammad et al 1996;Mahaffey and Annest 1986;Markowitz et al 1990;Szold 1974;Watson et al 1980Watson et al , 1986Wright et al 1999;Yip et al 1981;Yip and Dallman 1984) that have shown negative associations between iron intake or iron status and blood lead levels. Despite this negative relationship between maternal dietary iron and infant lead levels, we found no significant association between mother's iron stores (serum ferritin) and newborn's blood lead levels in bivariate or multivariate analysis (data not shown), mirroring the results of Milman and colleagues (1988).…”
Section: Discussionsupporting
confidence: 83%
“…Offspring of iron-replete dams exposed to 3% Pb acetate in food and 0.2% in drinking water were intravenously injected with Tf-bound 59 Fe. The results showed no effects on brain and kidney iron uptake and enhanced uptake in the liver (Crowe and Morgan, 1996). …”
Section: Introductionmentioning
confidence: 99%
“…Pb, along with other divalent metals, can be transported by DMT1 [222,223]. Iron deficiency in both animals and humans results in increased blood Pb levels [224,225]. Moreover, Wang et al [212,226] demonstrated that iron supplementation reduces both blood and brain Pb levels in the rats exposed to Pb and therefore provides a protective role against Pb-induced brain toxicity.…”
Section: Leadmentioning
confidence: 99%